MANAJEMEN MUTU PENDIDIKAN PADA SMP NEGERI 1 SIGLI KABUPATEN PIDIE - Heri Suwardi; Cut Zahri Harun; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The quality of education is a picture of the overall performance of service in an educational institution. Optimal service will yield optimal results anyway and is able to meet the expected demand by a core component of the education system. The purpose of this study was to obtain information about (1) the curriculum management at State Junior High School (SMP Negeri) No 1 of Sigli, Pidie Regency, (2) student management at SMPN 1 of Sigli Pidie (3) personnel management at SMP Negeri 1 of Sigli, Pidie, and (4 ) facilities and infrastructure management at SMP Negeri 1 of Sigli, Pidie Regency. This study used a qualitative approach and descriptive methods. Data were collected through observation, interviews and documentation study. Subjects of this study were the principal, the vice principal for student affairs, vice principal for curriculum affairs, and teachers at SMP Negeri 1 of Sigli, Pidie Regency. The results showed that: (1) curriculum management has been implemented by work programs, program implementation, supervision, and implementation of the learning process optimally; (2) student management has been done well by showing some indicators, such as an increase of students’ discipline, run extracurricular activities, the student development, and evaluation of student activities that have been implemented; (3) personnel management has also been implemented, although not optimal; this reality was true by not giving regular professional development of teachers. In addition, there were employees who were not professional, that is, those who taught the lesson which was not their major; and (4) management of facilities and infrastructure has also been implemented to the maximum, level of completeness of infrastructure and facilities were adequate and can be utilized effectively to improve the quality of education at SMP Negeri 1 of Sigli, Pidie Regency.Keywords: management, quality management, and education quality